“Everyone should have done a better job” - How Language Constructs Legitimacy in a Financial Scandal - Rysjö Lindholm,Ebba; Loudd,Tilda (2025)
Seminar date: June 4, 2025 Course: BUSN79 Authors: Ebba Rysjö Lindholm and Tilda Loudd Advisor/Examiner: Niklas Sandell/Liesel Klemcke Five key words: Account Theory, Legitimacy Theory, Crisis Communication, Allra, Financial Scandal Purpose: To examine how Allra, the Pensions Agency, Politicians, and Auditors used external communication to legitimize their actions throughout the Allra scandal, how these strategies evolved over time through verbal accounts, and what implications they had for shaping the Allra-story. Methodology: This study follows a longitudinal case study design of the Allra scandal. External communication from 2017 to 2025 was chronologically coded using Account theory and analyzed using Legitimacy theory to trace how legitimacy strategies evolved. Theoretical perspectives: This study is grounded in a constructionist perspective and draws on Account theory and Legitimacy theory. Empirical foundation: The study draws on secondary data from external communication, by Allra, the Pensions Agency, Politicians, and Auditors, including statements, interviews, reports, and media coverage from 2017–2025. Conclusions: This study shows how actors in the Allra scandal used verbal accounts to manage legitimacy. While Allra shifted strategies and reinforced its role as the main antagonist, other actors maintained consistent approaches that aligned with public expectations. In doing so, they protected their own legitimacy and helped frame Allra as the scandal’s villain.
Keywords: Account Theory; Legitimacy Theory; Crisis Communication; Allra; Financial Scandal